Subjunctive aspects of sociological support of the modern teacher formation process in the development context of the new Ukrainian school system - Hlebova, Natalia; Oleksenko, Karina; Oleksenko, Roman; Afanasieva, Lyudmila (Linguistics and Culture Review, 2021)
Purpose. Consider the subjunctive aspects of sociological support of the modern teacher formation process in the development context of the New Ukrainian School system. Theoretical basis. Theoretical basis is social and humanistic concepts of socio-philosophical, cultural, sociological, social and psychological approaches to the study of social factors in full Ukrainian school graduate adaptation in the broad context of socio-cultural realities. Scientific novelty. Based on the sociological design methodology and empirical research materials analysis of the educational and pedagogical environment state, an attempt has been made to identify the possibility of sociological procedures integration to identify the mutual influence of the educational process subjects in the modern school. Findings. It is summarized that such forms of modern teacher feedback on methods and work results as sociological assessment of stakeholder positions is an important aspect of supporting the new Ukrainian school development process. Based on the sociological assessment of priority mechanisms to improve the teaching efficiency, the respondents’ qualification level as information network users and potential factors for improving their skills, the topical directions for increasing the productivity of using social networks for educational communication were identified.